Capacitive sensing for the detection of tile misalignment in ceramic armor arrays. (June 2020) - Genest, Marc; Krys, Dennis; Mandache, Catalin
Abstract: The capacitive nondestructive technique uses a planar, two- or multi-terminal device to detect dielectric changes in its proximity. The technique has the advantages of being non-contact and requiring single-side access to the inspected test-piece. In this work, it is employed to determine the misalignment of ceramic tiles in two-dimensional array arrangements, as used for armored vehicles. Ceramic materials provide protection against projectile penetration in military and security applications. Tile assemblies are manufactured as protective add-on layers to armored vehicles. To provide effective protection, arrangements of rectangular or hexagonal tiles have to minimize potential misalignment, such as inter-tile gaps and out-of-plane mismatch. In this study, three planar capacitive probes with triangle-shaped terminals are used for the investigation of linear arrays of rectangular alumina tiles. Numerical simulations were employed to understand the probe's design parameters, as well as coupling aspects. It was found that the size of the capacitive probe and the separation between terminals provide a balance between spatial resolution, penetrability, and sensitivity to dielectric changes. Inter-tile gaps down to at least 0.5 mm, as well as out-of-plane tile misalignment as small as 0.25 mm were successfully discriminated.